Meningkatkan Kemampuan Guru dalam Membuat Modul Pembelajaran - Udin Erawanto; Miranu Triantoro; Hesty Puspita Sari; Yusniasri Primasari (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
The training is aimed to add scientific insight and increase teachers’s ability and quality to make learning modules independently adapted to the character of the subjects and the needs of students. Methods of lecture service activities are varied and practical or clinic. The training participants were all subject teachers for SMA Al Muhafizhoh, totaling 18 people, held for 2 days in the meeting room. Training results: 1) seen from the pre-test and post-test result comparisons there is an increase in scientific insight and ability in making learning modules, 2) all training participants (100%) can complete making learning modules according to the character of the subjects and student needs even though there are still revisions, including questions with HOTS character, the increasing of the number and variety is important. The training activities ran smoothly as expected because they received support from the foundation and institutions as well as school administrative staff in the form of adequate staff, minds, budgets and facilities in addition to the high level of participation of the training participants in participating in the activities. The problem is the limited implementation time.